2020
DOI: 10.3758/s13423-020-01847-z
|View full text |Cite
|
Sign up to set email alerts
|

Working memory limits severely constrain long-term retention

Abstract: There has been considerable controversy in recent years as to whether information held in working memory (WM) is rapidly forgotten or automatically transferred to long-term memory (LTM). Although visual WM capacity is very limited, we appear able to store a virtually infinite amount of information in visual LTM. Still, LTM retrieval often fails. Some view visual WM as a mental sketchpad that is wiped clean when new information enters, but not a consistent precursor of LTM. Others view the WM and LTM systems as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 56 publications
7
57
0
Order By: Relevance
“…Yet, no study has definitively established whether these distortions reflect lasting changes to memory content. In line with prominent theories and previous empirical evidence, we hypothesized that systematic distortions caused by perceptual comparisons would occur when LTM representations are recalled back into VWM (Cowan, 2001;Fukuda & Woodman, 2017;Sutterer et al, 2019) and that these distortions would be reported again during a subsequent retrieval episode (Atkinson & Shiffrin, 1968;Forsberg et al, 2020;Fukuda & Vogel, 2019).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Yet, no study has definitively established whether these distortions reflect lasting changes to memory content. In line with prominent theories and previous empirical evidence, we hypothesized that systematic distortions caused by perceptual comparisons would occur when LTM representations are recalled back into VWM (Cowan, 2001;Fukuda & Woodman, 2017;Sutterer et al, 2019) and that these distortions would be reported again during a subsequent retrieval episode (Atkinson & Shiffrin, 1968;Forsberg et al, 2020;Fukuda & Vogel, 2019).…”
Section: Discussionsupporting
confidence: 53%
“…Extant evidence of SIMB is restricted to simple visual features (e.g., color, shape) and has not yet been investigated in complex stimuli that individuals encounter in daily life (e.g., real-world objects). Relatedly, mounting evidence suggests that VWM serves as a "bottleneck" for perceptual input that is encoded into long-term memory (LTM; e.g., Atkinson & Shiffrin, 1968;Forsberg et al, 2020;Fukuda & Vogel, 2019) and a buffer for information that is reactivated from LTM (e.g., Cowan, 2001;Fukuda & Woodman, 2017;Sutterer et al, 2019). If endorsing similarity with novel visual input universally biases VWM representations, we should expect that LTM representations are prone to SIMB when retrieved and that SIMB can persist across time when retrieved representations return to their latent state.…”
Section: Comparing a Visual Memory To Novel Visual Input Risks Lasting Memory Distortionmentioning
confidence: 99%
“…It is therefore unsurprising that there is a recent interest in this kind of research. For instance, working memory theorists are examining the consequences of working memory tasks for long-term learning using a variety of manipulations of the processing at the time of encoding and maintenance in working memory (e.g., Bartsch et al, 2018 ; Forsberg et al, 2021 ; Loaiza et al, 2011 ; Loaiza & McCabe, 2012 ; McCabe, 2008 ; Rose & Craik, 2012 ; Souza & Oberauer, 2017 , 2018 for a recent review see Oberauer, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…The present contribution is to quantify the retrievable information in LTM in terms of information previously in WM, from the early elementary school years to adulthood. It has long been understood that WM serves as a portal to LTM (e.g., Atkinson & Shiffrin, 1968;Bartsch et al, 2019;Cowan, 1988Cowan, , 2019Forsberg et al, 2020;Fukuda & Vogel, 2019 ;Loaiza et al, 2021), albeit to an extent that seems methods-dependent (Shimi & Logie, 2019). There are, however, alternative potential scenarios for the childhood development of that portal for LTM.…”
Section: Introductionmentioning
confidence: 99%